2016
DOI: 10.1080/13642987.2016.1262520
|View full text |Cite
|
Sign up to set email alerts
|

Children’s rights to participation and protection in international development and humanitarian interventions: nurturing a dialogue

Abstract: This introduction provides the rationale for the special issue of the International Journal of Human Rights on the topic of the children's right to participation and protection in international development and humanitarian efforts. It summarises selected contributions relating to an international conference entitled 'Facilitating Child Participation in International Child Protection' that took place 5-6 October 2015 at Ryerson University in Toronto (Canada). The concepts of child participation and child protec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
33
0
4

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 50 publications
(38 citation statements)
references
References 15 publications
1
33
0
4
Order By: Relevance
“…Overall, participation is widely viewed as a right (e.g. Acero, 2011; Ajodhia‐Andrews, 2016; Collins, 2017; Cussiánovich, 2013; Gallego‐Henao, 2015; Graham, 2007; KII, academic, May; KII, academic, June; KII, consultant, June; Nour, 2013; Pavez‐Soto, 2012; Ruiz‐Casares et al, 2017; Streuli et al., 2009; Theis, 2007). According to the UN, child participation involves ‘…ongoing processes, which include information‐sharing and dialogue between children and adults based on mutual respect, and in which children can learn how their views and those of adults are taken into account and shape the outcome of such processes’ (UN Committee on the Rights of the Child, 2009, p. 5).…”
Section: Conceptualisationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Overall, participation is widely viewed as a right (e.g. Acero, 2011; Ajodhia‐Andrews, 2016; Collins, 2017; Cussiánovich, 2013; Gallego‐Henao, 2015; Graham, 2007; KII, academic, May; KII, academic, June; KII, consultant, June; Nour, 2013; Pavez‐Soto, 2012; Ruiz‐Casares et al, 2017; Streuli et al., 2009; Theis, 2007). According to the UN, child participation involves ‘…ongoing processes, which include information‐sharing and dialogue between children and adults based on mutual respect, and in which children can learn how their views and those of adults are taken into account and shape the outcome of such processes’ (UN Committee on the Rights of the Child, 2009, p. 5).…”
Section: Conceptualisationsmentioning
confidence: 99%
“…English‐language and Latin American articles revealed unique challenges in the implementation of children's rights to participation in child protection (McCafferty, 2017; Ruiz‐Casares et al, 2017; Seim & Slettebø, 2017; Tisdall, 2017). Many referred to barriers and limitations related to children's participation (Evans, 2009; Fylkesnes et al., 2018; Sancho & Cáceres, 2017; Cussiánovich, 2013; Pavez‐Soto, 2012; Toros et al., 2018; van Bijleveld et al., 2015) and the tensions between participation and protection (Bennouna et al., 2017; Cody, 2017; Collins, 2017; Holt, 2018; Sanders & Mace, 2006).…”
Section: Interconnections Of Rights Are Underappreciatedmentioning
confidence: 99%
“…The convention targets many levels where actions and support for children's protection, participation, and provision should occur. The Convention on the Rights of the Child balances the rights of children to the level of their families and the state and emphasizes the role and support of families and, on the other hand, the circumstances when the state has to intervene in family life if there are concerns about protection [21]. Therefore, there is a dependence between the child, family, and state, but there are differences in how child protection is regulated in different child welfare systems and policies [22,23].…”
Section: The Convention Of the Rights Of The Childmentioning
confidence: 99%
“…United Nations have set regulations for effective and respectful protection of children's rights, which include also their participation (United Nations General Assembly -UNGA, 1989). Ruiz-Casares et al (2016) state, that children should be seen 'as survivors and active participants in creating solutions, not just as victims and problems'. Despite that, Schalkers et al (2016) found out, that healthcare professionals think that children are not active participants in health care.…”
Section: Right To Information and Participationmentioning
confidence: 99%